2010
DOI: 10.1177/1475921710373294
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the defect localization capability of a guided wave SHM system applied to a complex structure

Abstract: Sparse-array structural health monitoring systems based on guided waves have been proposed by many authors, current signals being compared with a baseline obtained when the structure was known to be defect free. An image of the structure in the form of a ‘C-scan’ map showing likely defect locations can be produced by combining information from different sensor pairs in the array. It is generally recognized that temperature compensation is essential for the method to work and various compensation methods have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
(88 reference statements)
0
42
0
Order By: Relevance
“…In delay-and-sum localization, we model the measured signal x n (t) at each receiver n as a delayed replica of the original excitation signal s(t) such that [9][10][11] x (j,k)…”
Section: Delay-and-sum Localization Standard Delay-and-sum Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In delay-and-sum localization, we model the measured signal x n (t) at each receiver n as a delayed replica of the original excitation signal s(t) such that [9][10][11] x (j,k)…”
Section: Delay-and-sum Localization Standard Delay-and-sum Localizationmentioning
confidence: 99%
“…In this paper, we instead utilize the multipath effects to improve localization performance. We present a simple pipe propagation model that we combine with the standard delay-and-sum localization technique [9][10][11], also known as the ellipse method. We show that the model can be used to account for multi-path effects and to significantly improve localization resolution along a pipe's circumference.…”
Section: Introductionmentioning
confidence: 99%
“…42, 43 An improved BSS method was proposed. 44 where different correction factors was used for each wave packet and it was shown that the baseline correction was valid for a wider range of temperature changes and applicable to both metallic and composite structures.…”
Section: Ugw Damage Detection Methodologies: Baseline Methodsmentioning
confidence: 99%
“…Many structural health monitoring strategies fail in varying environmental conditions because they directly compare current measurements with a single earlier baseline measurement [13], [28], [29]. For example, Fig.…”
Section: Variabilitymentioning
confidence: 99%